The Role Of Information And Innovative Technologies In Teaching Kazakh - Gulzhaina Nurmanova, Aisulu Nurzhanova, Raikhan Abnasyrova, Maira Zholshayeva, Khafiza Ordabekova, (Opción, 2019)
The aim of the study is to investigate the role of information technologies in teaching Kazakh via method of modeling and transformation, method of integrated education and the method of gamification in teaching Kazakh as a foreign language. The results of this research will impact the development of teaching Kazakh as a foreign language, its recognition and competitiveness at the international scientific level. In conclusion, an innovative component in teaching Kazakh as a foreign language allows students to activate the process of mastering the material, as well as prepare for the exam.